Digital Preservation Policies, Strategies, and Challenges in University Libraries: A Systematic Review - Andi Saputra; Desriyeni; M. Giatman (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2026)
Background of the study: In the post-COVID-19 Pandemic era, digital preservation is a crucial strategy for preserving collections in university libraries. Purpose: The primary objective is to gain a comprehensive understanding of the policies, strategies, and challenges associated with repository-based digital preservation in university libraries. Method: This study uses a systematic literature review with the PRISMA framework to select, assess, and synthesize evidence from Google Scholar. Out of Scopus-indexed references (2018-2025), 19 relevant articles met the inclusion criteria. Findings: Digital preservation is a major focus in Asia and Africa (nearly 85% of literature), with significant contributions from Pakistan. Key obstacles include a lack of formal policies, limited budgets, insufficient staffing, and obsolete technology. Developing nations rely on backups, replication, and migration, while developed countries utilize advanced techniques like web scraping. Conclusion: This research presents an in-depth study of digital preservation policies, strategies, and challenges. The findings assist researchers and practitioners in maintaining access to digital intellectual heritage and guide policymakers in managing repository-based digital content preservation.